2021
DOI: 10.1155/2021/5593919
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oxidative Balance Score with the Metabolic Syndrome in a Sample of Iranian Adults

Abstract: Objective. We aimed to assess the association of the oxidative balance score (OBS) with metabolic syndrome (MetS) in adults. Design. A population-based cross-sectional study Setting. Health centers from five districts in Tehran, Iran. Methods. We recruited 847 participants with an age range of 18-65 years. Dietary intake was assessed by a semiquantitative food frequency questionnaire with 168 items. The OBS was calculated by using the following 13 dietary and nondietary anti- and prooxidant components: dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
2
19
2
Order By: Relevance
“…However, vitamin C intake was lower in the abdominal obesity group than in the control group in both genders, and these results were consistent with those in previous studies in different ethnicities and ages ( 33 , 34 ). The difference in vitamin C is associated with a higher intake of fruit and fruit juice, including fruit juice, in both genders.…”
Section: Discussionsupporting
confidence: 92%
“…However, vitamin C intake was lower in the abdominal obesity group than in the control group in both genders, and these results were consistent with those in previous studies in different ethnicities and ages ( 33 , 34 ). The difference in vitamin C is associated with a higher intake of fruit and fruit juice, including fruit juice, in both genders.…”
Section: Discussionsupporting
confidence: 92%
“…The overall OBS was stratified by the upper tertile cutoff value of 19 and lower tertile cutoff value of 15 ( Noruzi et al, 2021 ). The dietary OBS was stratified by the upper and lower tertile cutoff values of 13 and 8, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative balance score (OBS) is an approach that evaluates the overall oxidative status in the body via the combined status of pro- and antioxidants ( Van Hoydonck et al, 2002 ). Previous studies have used 12–14 pro- and antioxidant factors related to nutrients, lifestyle, body composition, and medical history for OBS calculation, with antioxidants contributing positively to the value and prooxidants contributing negatively to the value ( Kong et al, 2015 ; Noruzi et al, 2021 ). The higher OBS has been associated with a lower risk of various non-communicable diseases and adverse outcomes, such as hypertension ( Annor et al, 2015 ), colorectal adenoma ( Dash et al, 2013 ), prostate cancer ( Lakkur et al, 2014 ), chronic kidney disease, and all-cause mortality ( Ilori et al, 2015 ; Kong et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study implemented in South Korea revealed a significant negative correlation between OBS and the risk of developing metabolic syndrome (MetS) [18]. Conversely, a subsequent study performed in Iran found no significant relationship between OBS and MetS in adults [19]. Our results extended these prior findings, corroborating that high OBS is not only remarkably linked to a decreased risk of hypertension, diabetes, and hyperlipidemia but also significantly correlated with a lower risk of CMRFs in US adults.…”
Section: Discussionmentioning
confidence: 99%